The Role of the Altman Z-Score Method in Predicting Corporate Bankruptcy - Raditya Prayata Putra Fai; Hana Rahmah Kamila; Faiza Ghefira Irwandi (INCOME: Innovation of Economics and Management, 2023)
The bankruptcy of a company can occurs due to various factors, one of which is the company's financial inability to pay its debts to creditors. With the assistance of predictive analytical models designed by several experts, including well-known methods like the Altman Z-Score analysis, the potential for bankruptcy can be detected earlier. This analytical model aims to provide early warnings regarding possible financial issues a company might face. The objective of this research is to analyze the role of the Altman Z-Score in predicting bankruptcy in a company. The research methodology employed includes literature review and library studies. The results of this research demonstrate the significant role of the Altman Z-Score analysis method in predicting the financial condition of a company based on its financial statement ratios.